Modeling and simulation of the mixing process of fluids in microchannels promoted by acoustic streaming - Catarino, Susana Oliveira (2011)
This work describes a study on the acoustic streaming phenomenon, for promoting mixing in microfluidic channels. Acoustic microagitation is a solution to overcome the slow molecular diffusion and accelerate chemical reactions, which is essential to the success of microfluidic devices. A preliminary study has been performed on the piezoelectric effect generated by an electroactive polymer and on the compressible flow Navier-Stokes equations. The simulations were based on finite elements numerical methods. It was concluded that the positioning of the transducer influences the pressure distribution over the fluid domain. It was also seen that the Navier-Stokes equations can be expanded as a sum of equilibrium, first and second order values, that describe the damped propagation of acoustic waves and the global flow, respectively. The time average of the first order results corresponds to a force and can be applied as a source term in the second order equations to determine the mean global flow into the microcuvette.